Investigation of the Thermal Performance of Energy Tunnel Equipped with the Insulation Layer Considering Ventilation and Groundwater Seepage. (9th August 2021) - Zhang, Guozhu; Cao, Ziming; Zhao, Xu; Xie, Yongli; Liu, Xiaohua; Cao, Shiding
Abstract : The insulation layer is usually installed in the tunnel structure, whereas the influence of the insulation layer on the thermal behavior of energy tunnel ground heat exchangers (GHEs) is rarely investigated. The model tests were performed in this study to evaluate the heat transfer potential of the energy tunnel with the insulation layer under ventilation and groundwater seepage. The results can be obtained as follows: first, the fluctuations of air temperature and surrounding rock temperature at different locations are relevant to insulation layer, ventilation, and groundwater seepage. Second, the reduction effect of ventilation on the interface temperature of tunnel lining and surrounding rock is alleviated when using an insulation layer, and the interface temperature at upstream section of groundwater seepage is more easily affected by the energy tunnel GHEs. Third, the variation range of ground temperature is wider at the downstream section of groundwater flow. Moreover, the heat exchange rates of tunnel without the insulation layer improve by 5.82% and 6.45% with increasing wind speed at two groundwater flow velocities of 1 × 10 − 4 and 5 × 10 − 4 m/s, and there are only 2.03% and 0.77% enhancements of heat exchange rates by ventilation for the tunnel with the insulation layer. However, the thermal performance of the energy tunnel improved by groundwater is less relevant to the existence of the insulation layer. The relevant findings can provide an effective guidance for the following research and design of the energy tunnel.